Green synthesis of nanostructured calcium ferrite particles and its application to photocatalytic degradation of Evans blue dye. (2022) - Adarsha, J.R.; Ravishankar, T.N.; Manjunatha, C.R.; Ramakrishnappa, T.
Highlights: We have successfully synthesized CaFe2O4 NPs via solution combustion synthesis using lemon juice as the fuel at 500 °C for excellent photocatalytic activity against Evans Blue dye. The physical and chemical properties of CaFe2 O4 nanostructure was established by different characterization techniques, including XRD, TEM, HRTEM, SAED, SEM, EDAX, BET, UV–Vis and FT-IR analyses. Green synthesis of efficient nanoparticles by simple solution combustion method which shows high specific surface area 142.5 m 2 g −1 . The synthesized CaFe2 O4 nanoparticles exhibit photocatalytic activity against Evans Blue dye and further degradation of dye was studied under varying pH, varying dosage of the catalyst, varying concentration of the dye. Recycle and reusability studies, it was clear that the prepared CaFe2 O4 nanostructureshowed good photostability. We have also studied isothermal models and kinetic models for the photocatalytic activity against Evans Blue dye. Abstract: In the present experimental investigation, green synthesis of nanostructured calcium ferrite (CaFe2 O4 ) particles by solution combustion method and its application to photocatalytic degradation of evans blue dye. Physico-chemical properties of the synthesized nanoparticles (NPs) were elucidated by TEM, HRTEM, SAED, SEM, EDAX, BET, UV–Vis and FT-IR analyses. The spherical NPs undergo photocatalytic followed by adsorption. The NPs Dispersive reflectance spectrum shows bandgap value 1.92 eV and maximum absorption at 220 nm. HRTEM divulgence the space lattice 0.25 nm with an average particle size of 45 nm. The surface of the NPs SEM micrograph shows huge pores and voids which enhances the adsorption along with photocatalytic degradation. The CaFe2 O4 NPs was optimized for the various photocatalytic followed adsorption parameters namely pH, the effect of dosage catalyst load, varying initial concentration of the dye. The maximum adsorption followed degradation capacity shows 42.42 mgg −1 (Nonlinear). The Sips model is the best-fitted isotherm equilibrium model with the least statistical errors and high correlation coefficient R 2 0.988 (Nonlinear) compared to other models. The pseudo-second-order model shows the higher correlation coefficient R 2 > 0.94 at all concentrations over other kinetic models. The Webber Morris model shows distinct linear phase shows Photocatalysis of degradation and adsorption follows a multistep mechanism. The study has shown it is possible to reuse the catalyst for adsorption and dye degradation with satisfactory efficiency for almost 5 cycles which indicates its photostability.